2016
DOI: 10.1186/s13045-016-0256-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative effects of T cells expressing a ligand-based chimeric antigen receptor against CD116 on CD34+ cells of juvenile myelomonocytic leukemia

Abstract: BackgroundJuvenile myelomonocytic leukemia (JMML) is a fatal, myelodysplastic/myeloproliferative neoplasm of early childhood. Patients with JMML have mutually exclusive genetic abnormalities in granulocyte-macrophage colony-stimulating factor (GM-CSF) receptor (GMR, CD116) signaling pathway. Allogeneic hematopoietic stem cell transplantation is currently the only curative treatment option for JMML; however, disease recurrence is a major cause of treatment failure. We investigated adoptive immunotherapy using G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Currently, anti-CD19 CAR-T cells were demonstrated to be effective in the treatment of B cell non-Hodgkin lymphoma (NHL), acute lymphoblastic leukemia (ALL), and chronic lymphocytic leukemia (CLL) [913]. Anti-CD116 has been developed for treating myelomonocytic leukemia [14].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Currently, anti-CD19 CAR-T cells were demonstrated to be effective in the treatment of B cell non-Hodgkin lymphoma (NHL), acute lymphoblastic leukemia (ALL), and chronic lymphocytic leukemia (CLL) [913]. Anti-CD116 has been developed for treating myelomonocytic leukemia [14].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Although studies of piggyBac-generated CAR T cells have consistently shown in vitro efficacy against their relevant targets,15,20,21,[32][33][34][35] this has not previously translated into sustained complete remissions of malignancy in vivo 21,34. A recent report by Morita et al described a novel method for manufacture of CAR19 T cells incorporating CD28 spacer and co-stimulatory domains 36.…”
mentioning
confidence: 99%
“…The PiggyBac, Sleeping Beauty and Tol2 transposons are all being explored for the transfer of CAR constructs, with CD19 being the typical target antigen [ 125 , 127 , 128 ]. Even so, transposon mediated gene transfer of CARs targeting mesothelin [ 129 ], CD56 [ 130 ], EGFR (epidermal growth factor receptor) [ 131 ], CD116 [ 132 ], IGF1R (insulin-like growth factor 1 receptor) and ROR1 (receptor tyrosine kinase like orphan receptor 1) [ 133 ] and HERV-K (human endogenous retrovirus-K) [ 134 ] have been reported. So far, clinical data is available from parallel Phase I trials where Sleeping Beauty was used to transfer a CD19 CAR to T cells which were used for the treatment of a total of 26 patients with advanced non-Hodgkin lymphoma or acute lymphoblastic leukemia.…”
Section: New Routes For Gene Transfer: Bringing the Car To The Celmentioning
confidence: 99%